A chegada dos Franciscanos ao Japão e o início da querela missiológica (Estudos Japoneses, 2017)
This study introduces an unreleased manuscript, whose authorship is unknown, and is placed in the Royal Academy of History in Madrid, about the quarrel that developed between the missionaries of different orders in the Japanese mission, in the late 16th and early 17th centuries. It deals with the beginning of the disputes about the primacy of the evangelization claimed by the Jesuits in the Land of the Rising Sun which clashed with the firm intention of the Franciscans in order to profess the Christian religion there. Despite the Papal Bull that conferred the Society of Jesus the monopoly over the mission in the archipelago, the discalced friars decided to continue the enterprise. This essay analyses the first Franciscans accusations that gave rise to a defense literature by the Jesuits. The results were no long in coming.